HUBUNGAN KARAKTERISTIK SIBLING DENGAN PERKEMBANGAN ANAK USIA PRASEKOLAH DI WILAYAH KERJA PUSKESMAS PURNAMA - Tri " Utanti; Oswati " Hasanah; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The new members in the family for a child create sibling characteristic. The relationship between sibling called sibling relationship. This research purposes to identify relationship between characteristic sibling with preschool children development on Purnama Community Health Centers with descriptive correlative dan cross sectional design. The sample was 80 respondents use accidental sampling, and data on this research collected using questioner and pre-screening development questioner. In this study, we use univariate and bivariate data with chi-square test.   The results showed that there was no correlation between all sibling characteristic (sex difference, age of sibling, interaction duration, numbers of siblings) and preschool children  (ρ value > α). This research recommends to health workers to continue doing screening on child development in preschool age. Keywords: Characteristics sibling, children preschool age development.